Making a living: pro poor tourism in hot spring recreational park of Sungai Klah, Sungkai, Perak, Malaysia - Che Leh Fauziah, Omar Baharudin, Ahmad Baharom Azmi (N/A, 2015)
Making a living: pro poor tourism in hot spring recreational park of Sungai Klah, Sungkai, Perak, Malaysia by Che Leh Fauziah, Omar Baharudin, Ahmad Baharom Azmi,